Rationality of Bejampik Medicine Service Users in Kemuja Village, West Mendo District, Bangka Regency - Marzuki Darusman; Iskandar Zulkarnain; Fitri Ramdhani Harahap (Profesional Muda Cendekia Publishing, 2023)
Health needs can be met through two methods of treatment, namely modern medicine method and traditional method. One example of traditional medicine method is bejampik treatment. Bejampik is closely related to the spirituality of people who adhere to islam in Bangka Belitung. The aims of this study were: 1) Finding out the social factors and effects resulting from the use of bejampik traditional medicine in a sustainable manner; and 2) Identifying and analyzing forms of community social action using bejampik traditional medicine. This research was conducted in Kemuja Village, West Mendo District, Bangka Regency in 2022 using a descriptive qualitative research method. The data used in this study are primary data and secondary data collected through semi- structured interview, observation, and documentation from 8 users of bejampik treatment service with several criteria. The data was analyzed using data analysis techniques which included data reduction, data presentation, and drawing conclusion. The result of this study indicate that: 1) The social implication that encourage people to use traditional bejampik medicine so that traditional medicine can survive in the modern era are divided into three, namely the trust of people in Bangka Belitung, the background of bejampik artisans who are well known by the people in Bangka Belitung, and the motivation of the people in Bangka Belitung; 2) The form of social action of bejampik users is divided based on the type of users, namely instrumental rational action on pure bejampik treatment users and value- rational action on mixed bejampik treatment users who are classified as rational action type of social action.